Case Report: A case of ovarian carcinoma manifesting with chest tightness as the initial clinical presentation accompanied by marked elevation of pleural effusion amylase levels - Ou, Guo-Yu; Zhu, Yin-Chuan; Li, Kun; Li, Cheng-Jie; Yi, Xin; Wan, Qiu-Bin; Shen, Hai-Lan (Frontiers in Oncology, 2026)
This article reports a case of ovarian cancer presenting with chest tightness as the initial symptom, accompanied by markedly elevated pleural fluid amylase. A middle-aged female patient sought medical attention for “chest tightness and wheezing” as her primary complaints. Imaging revealed a massive pleural effusion with significantly elevated serum and pleural fluid amylase levels. Pleural fluid cytology staining and ovarian tissue pathology confirmed the diagnosis of high-grade serous carcinoma of the ovary. Subsequently, she underwent open abdominal cytoreductive surgery for ovarian cancer under general anesthesia, which included total hysterectomy, bilateral salpingo-oophorectomy, and omentectomy. Adjuvant chemotherapy with paclitaxel and carboplatin was administered two weeks after surgery. Amylase levels returned to normal after four weeks. This case suggests that in female patients with unexplained abnormally elevated serum and body fluid amylase levels, clinicians should remain vigilant for the possibility of ovarian cancer. Amylase may serve as an auxiliary diagnostic clue, and its combination with pathological and imaging examinations can facilitate early differentiation. Clinical practice should emphasize the diagnostic value of atypical symptoms and laboratory indicators.